Open fourth ventricle prior to 20 weeks' gestation: a benign finding?. (4th February 2014) - Contro, E.; Volpe, P.; De Musso, F.; Muto, B.; Ghi, T.; De Robertis, V.; Pilu, G.
ABSTRACT Objective To evaluate the role of the brainstem–vermis (BV) angle in the diagnosis of fetal posterior fossa abnormalities at 15–18 weeks' gestation. Methods We examined retrospectively three‐dimensional (3D) ultrasound volumes acquired at 15–18 gestational weeks in fetuses with normal posterior fossa (controls) and in those with cystic posterior fossa. Whether the fourth ventricle appeared open posteriorly in axial views was noted and the BV angle was measured. A detailed follow‐up was obtained in all cases. Results Of the 139 controls, 46 cases were excluded because of inadequate quality of the 3D volumes. Of the 93 remaining normal fetuses, 84 (90.3%) had a closed fourth ventricle and a BV angle < 20°, whereas 9/93 (9.7%) had an open fourth ventricle and a BV angle between 20° and 37°. The study group of 11 fetuses included seven with Dandy–Walker malformation and four with Blake's pouch cyst. In abnormal cases as a whole, the BV angle was significantly increased compared with that in controls (P < 0.0001). However, fetuses with Blake's pouch cyst and normal fetuses with an open fourth ventricle had strikingly similar sonograms: the BV angle was between 20° and 37° and the fourth ventricle appeared open only when viewed using a more steeply angulated scanning plane than that of the standard transcerebellar plane; in fetuses with Dandy–Walker malformation the fourth ventricle was widely open posteriorly, even in the standard transcerebellar view, and the BV angle was > 45°, significantly increased compared both with that in normal fetuses (P < 0.0001) and with that in fetuses with Blake's pouch cyst (P = 0.004). Conclusion An open fourth ventricle is found in about 10% of normal fetuses at 15–18 weeks' gestation. Measurement of the BV angle is useful in such cases, as a value ≥ 45° is associated with a very high risk of severe posterior fossa malformation. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.